Pengaruh Motivasi Kerja Terhadap Kinerja Guru Sekolah Dasar “ XYZ” Pekabaru - Rofidah, Siti; Putra, Eka (Eko dan Bisnis: Riau Economic and Business Review, 2024)
The research conducted at XYZ analyzed data using descriptive and quantitative methods to compare actual reality with theories. The data was tabulated and analyzed according to research objectives. The results showed that respondents strongly agreed with the motivation variable (X) and agreed with the performance variable (Y). The regression equation derived from the research indicated that when the motivation value is 0, teacher performance is positive at 9.829. The motivation coefficient value of 0.734 suggested that a unit increase in motivation led to a 73.4% change in teacher performance. The R Square (R2) value of 0.520 indicated that 52.0% of the teacher performance at SD XYZ in Pekanbaru can be explained by motivation, while the remaining 48.0% is influenced by other factors not examined in the research.